IFT140+/K14+ cells function as stem/progenitor cells in salivary glands - Xueming Zhang; Ji Zhou; Xinyu Wang; Jiangyu Geng; Yubei Chen; Yao Sun (Nature Publishing Group, 2022)
Abstract Stem/progenitor cells are important for salivary gland development, homeostasis maintenance, and regeneration following injury. Keratin-14+ (K14+) cells have been recognized as bona fide salivary gland stem/progenitor cells. However, K14 is also expressed in terminally differentiated myoepithelial cells; therefore, more accurate molecular markers for identifying salivary stem/progenitor cells are required. The intraflagellar transport (IFT) protein IFT140 is a core component of the IFT system that functions in signaling transduction through the primary cilia. It is reportedly expressed in mesenchymal stem cells and plays a role in bone formation. In this study, we demonstrated that IFT140 was intensively expressed in K14+ stem/progenitor cells during the developmental period and early regeneration stage following ligation-induced injuries in murine submandibular glands. In addition, we demonstrated that IFT140+/ K14+ could self-renew and differentiate into granular duct cells at the developmental stage in vivo. The conditional deletion of Ift140 from K14+ cells caused abnormal epithelial structure and function during salivary gland development and inhibited regeneration. IFT140 partly coordinated the function of K14+ stem/progenitor cells by modulating ciliary membrane trafficking. Our investigation identified a combined marker, IFT140+/K14+, for salivary gland stem/progenitor cells and elucidated the essential role of IFT140 and cilia in regulating salivary stem/progenitor cell differentiation and gland regeneration.